The Legality of Okinotorishima’s Islandization under UNCLOS: Implications for Indonesia’s Basepoint Preservation Strategies - Widiastuti, Tri; Musyarri, Fazal Akmal (CV. Social Politic Genius (SIGn), 2025)
The escalation of maritime realism in East Asia has driven coastal states to manipulate the characteristics of geographical features using advanced technology to expand jurisdiction, a phenomenon that has manifested in its most extreme form in the Okinotorishima dispute. This research aims to analyze the legal validity of Japan’s technological interventions to maintain Okinotorishima’s status as an island under the UNCLOS regime. Utilizing a normative legal research method within an interdisciplinary framework, this study conducts a juridical examination of Ocean City’s planning research and the mass coral propagation project (coral pegs). These technical facts are then tested dialectically using the natural condition doctrine and the jurisprudence of the 2016 PCA Award. The results show that although the concrete infrastructure and bio-engineering successfully prevent physical erosion, this success lacks legal equivalence. Such artificial modifications are considered installations that fail to meet the natural capacity requirements to sustain life, rendering the feature’s status as a “rock” not entitled to an Exclusive Economic Zone. This research identifies this practice as an Islandization strategy, a form of lawfare that uses technology to create material hegemony atop a legal legitimacy void. As a strategic implication, the research recommends that Indonesia reject such an artificial expansion model and adopt the Eco-Technological Defense paradigm. This strategy focuses on restoring the ecological functions of basepoints on outermost small islands threatened by abrasion, such as in Bengkalis and Natuna, to secure sovereignty without violating the integrity of the international law of the sea.